Linking Learning Achievement in Creative Product and Entrepreneurship Subject to Entrepreneurial Interest: A Case Study of Fashion Design Students at a Vocational School in Semarang - Riska, Avinda Fachri Eliana; Nurmasitah , Sita (Universitas Negeri Semarang, 2025)
The Creative Product and Entrepreneurship subject is designed to equip vocational students with essential knowledge in production and marketing based on their specialization. This study investigates the relationship between students' learning achievement in the CPE subject and their entrepreneurial interest among Fashion Design students at SMK Mataram Semarang. Employing a quantitative approach, this research involved 21 students from grade XI (10 students) and grade XII (11 students). Data were collected using documentation methods to obtain formative, summative, and practical scores and a questionnaire to assess entrepreneurial interest. The data analysis utilized the Pearson Product Moment correlation test, preceded by normality and linearity tests. The findings revealed a significance value of 0.984, exceeding the critical value of 0.433. This result indicates a significant positive relationship between CPE learning achievement and students’ entrepreneurial interest. The study suggests that enhancing CPE instruction can foster students' entrepreneurial mindset, particularly in vocational education settings such as Fashion Design programs.